Analisis Korelasi Karakteristik Inovasi dengan Adopsi Pengendalian OPT Ramah Lingkungan pada Usahatani Cabai di Kabupaten Manokwari, Papua Barat - Tapi, Triman; Mikhael, Mikhael; Tapi, Mathius (Suluh Pembangunan : Journal of Extension and Development, 2025)
Environmentally friendly pest control in chili cultivation is a crucial strategy to minimize the negative effects of chemical pesticide use on ecosystems and human health. However, farmers’ adoption of this innovation remains relatively low, especially in Desay Village, Prafi District, Manokwari Regency. This study aimed to analyze the adoption process of environmentally friendly pest control practices, identify the influencing factors, and examine the relationship between specific innovation characteristics and the level of farmer acceptance. A mixed-methods approach was employed, combining quantitative data from questionnaires distributed to 45 chili farmers with qualitative data gathered through in-depth interviews and field observations. Descriptive analysis was used to identify adoption patterns, and Spearman rank correlation was applied to assess relationships between innovation characteristics and adoption stages. The results showed that despite general awareness and interest, adoption levels remained low. Major barriers included perceived risks, limited resources, and insufficient technical support. Characteristics such as compatibility, trialability, and observability were significantly and positively correlated with adoption. Farmers were more likely to adopt innovations that suited local conditions, were easy to test, and offered visible benefits. These findings highlight the need to strengthen technical assistance, implement field demonstrations, and promote adaptive education strategies that align with local farming contexts to improve adoption of sustainable pest control innovations.